2018
DOI: 10.1002/chem.201800447
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Heme Iron Catalysts for Olefin Epoxidation: Conformationally Rigid Aryl–Aryl Junction To Support Amine/Imine Multidentate Ligands

Abstract: Atom-transfer chemistry represents an important class of reactions catalyzed by metalloenzymes. As a functional mimic of non-heme iron enzymes that deliver oxygen atoms to olefins, we have designed monoiron complexes supported by new N-donor chelates. These ligands take advantage of heme-like conformational rigidity of the π-conjugated molecular backbone, and synthetic flexibility of tethering non-heme donor groups for additional steric and electronic control. Iron complexes generated in situ can be used to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…The dpap ligand system is based on the N3 ligand 2 (Figure 2 a) which we recently reported for biomimetic iron chemistry [15] . The first‐generation tridentate ligand 2 was prepared by installing a flexible pyridyl pendant to the rigid and π‐conjugated anilido‐pyridyl [ N , N ]‐bidentate motif 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dpap ligand system is based on the N3 ligand 2 (Figure 2 a) which we recently reported for biomimetic iron chemistry [15] . The first‐generation tridentate ligand 2 was prepared by installing a flexible pyridyl pendant to the rigid and π‐conjugated anilido‐pyridyl [ N , N ]‐bidentate motif 3 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2 b, the amide carbonyl group of the dpap ligand is not directly coordinated to the metal, but protonation or metal‐binding to this secondary coordination sphere can reversibly modulate the relative contribution of the amido vs. iminol/iminolate Lewis structure descriptions in resonance, thereby enabling remote control of the ligand donor ability [16] . The ligand H‐dpap was conveniently prepared by an amide coupling reaction between 3 [15] and 4 [17] in excellent yield (>95 %) (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…[13,[61][62][63][64][65][66] Further,t he small negative value of the reaction constant is similar to some of the reported high-valent iron-oxo and iron(III)-acylperoxo complexes. [17,49,62] Thereafter,w eh ave carried out kinetics of the different internal olefins.W eh ave studied the second-order kinetics of cis and trans-stilbene.Itwas found that the secondorder rate constant, (k 2 % 1.12 M À1 S À1 )o ft he trans isomer is almost ten times of the cis-stilbene (k 2 % 0.141 M À1 S À1 ). The higher olefin epoxidation rate of the trans-stilbene can be rationalized by the lower one-electron oxidation potential of the trans-stilbene compared to cis-stilbene.…”
Section: Resultsmentioning
confidence: 99%
“…As a first step to realize the idea outlined in Figure 1 b, we designed the simplest molecular prototype [ 1‐Me ]Cl (Scheme 1 b). This compound was prepared by following the general synthetic protocol outlined in Scheme 1 a, starting with methylation of the anilido‐pyridine precursor A , [13] followed by acid‐catalyzed condensation reaction with formaldehyde in HCl/1,4‐dioxane (Scheme S1) [14] . The resulting yellow precipitate was isolated by simple filtration.…”
Section: Resultsmentioning
confidence: 99%